The Influence of Contribution and Effectiveness of Regional Taxes on Original Regional Income (PAD) in Palembang City - Yo Vira Towi; Emilia Gustini; Aris Munandar (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to analyze the effect of contribution and effectiveness on local revenue (PAD) in Palembang City. The data used in this research is secondary data in the form of documentation and literature study. The research method used is multiple linear regression analysis. The results indicate that the contribution and effectiveness have a significant effect on local revenue (PAD). This research is expected to become additional literature on the topic of local revenue (PAD).